Evaluation of vilazodone for the treatment of depressive and anxiety disorders. (11th February 2019) - Stuivenga, Mirella; Giltay, Erik J.; Cools, Olivia; Roosens, Laurence; Neels, Hugo; Sabbe, Bernard
ABSTRACT: Introduction : Major Depressive Disorder (MDD) and General Anxiety Disorder (GAD) significantly contribute to the global burden of disease. Vilazodone, a combined serotonin reuptake inhibitor and 5-HT1A partial agonist, is an approved therapy for the treatment of MDD and which has been further investigated for GAD. Areas covered : This article covers the pharmacokinetics and pharmacodynamics of vilazodone and provides an evaluation of the clinical usefulness of vilazodone for the treatment of MDD and anxiety disorders. A literature search was performed using PubMed/MEDLINE, Web of Science and the Cochrane Library. Expert opinion : Studies have shown that vilazodone is significantly superior to placebo. However, vilazodone cannot as yet be recommended as a first-line treatment option for MDD as it is unclear whether the drug's dual mechanism of action provides greater efficacy than prevailing treatment options. Moreover, more phase IV studies are needed to establish its efficacy and long-term safety in larger and more diverse populations. Although vilazodone may have an additional advantage for the treatment of anxiety symptoms in MDD, here also additional studies are required to confirm its efficacy over and above SSRI alternatives and other antidepressant treatments. Therefore, presently, vilazodone should be considered as a second- or third-line treatment option for MDD and GAD.